Financial Performance Analysis Based on the Economic Value Added Method at PT. Indofood Successfully Prosperous TBK for the 2020-2022 Period - Febria Rahmah Dian Fidain; Syamsul Arifin (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
EVA is one of the methods used to measure a company's financial performance in evaluating added value, where added value is used as a benchmark by capital owners when deciding how much investment to spend on the company. The application of the EVA model is very useful to be used as a measurement of company performance where the focus of performance appraisal is the creation of added value. This research uses a descriptive analysis method with a quantitative approach whose data is expressed in the form of numbers and analysis in the form of basic data accumulation in descriptive form from the data that has been collected. The purpose of this study is to determine the level of financial performance of companies using the EVA method at PT. Indofood Sukses Makmur Tbk in 2020-2022. The results of this study show positive developments in 2020-2021, namely EVA > 0, where there has been economic added value and financial performance can be said to be good, while in 2022, EVA < 0, which means that it has not been able to provide economic added value, indicating that the company's financial performance is not good.